Genome-wide analysis of tandem repeats in Tribolium castaneum genome reveals abundant and highly dynamic tandem repeat families with satellite DNA features in euchromatic chromosomal arms - Pavlek, Martina (DNA Res, 2015)
Although satellite DNAs are well-explored components of heterochromatin and centromeres, little is known about emergence, dispersal and possible impact of comparably structured tandem repeats (TRs) on the genome-wide scale. Our bioinformatics analysis of assembled Tribolium castaneum genome disclosed significant contribution of TRs in euchromatic chromosomal arms and clear predominance of satellite DNA-typical 170 bp monomers in arrays of ≥5 repeats. By applying different experimental approaches, we revealed that the nine most prominent TR families Cast1–Cast9 extracted from the assembly comprise ∼4.3% of the entire genome and reside almost exclusively in euchromatic regions. Among them, seven families that build ∼3.9% of the genome are based on ∼170 and ∼340 bp long monomers. Results of phylogenetic analyses of 2500 monomers originating from these families show high-sequence dynamics, evident by extensive exchanges between arrays on non-homologous chromosomes. In addition, our analysis shows that concerted evolution acts more efficiently on longer than on shorter arrays. Efficient genome-wide distribution of nine TR families implies the role of transposition only in expansion of the most dispersed family, and involvement of other mechanisms is anticipated. Despite similarities in sequence features, FISH experiments indicate high-level compartmentalization of centromeric and euchromatic tandem repeats.